PENGARUH PENDIDIKAN AGAMA ISLAM TERHADAP PENCEGAHAN BULLYING (MTS AL-WASLIYAH PONDOK KOPI JAKARTA TIMUR) - Putri Aisyah; Syarullah; Kamilatul Millah; Nahuda Alwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted because many students are still found to be victims of bullying at school. This phenomenon has become a serious concern because it can negatively affect students' mental health and academic achievement. Therefore, this study aims to analyze the influence of Islamic Religious Education on bullying prevention among students at MTs Al-Washliyah, East Jakarta. This research employed a quantitative method using a survey approach. Data were collected through questionnaires, observations, and documentation. The study involved 76 seventh- and eighth-grade students selected using a total sampling technique. The results of the correlation analysis indicated a positive and significant relationship between the two variables, with a correlation coefficient (rxy) of 0.686. The significance value (Sig. 1-tailed) was 0.000, which is lower than the significance level of 0.05, indicating that the relationship is statistically significant. Furthermore, the coefficient of determination (R²) was 0.470, meaning that 47% of the variation in bullying prevention behavior can be explained by Islamic Religious Education.The findings demonstrate that Islamic Religious Education plays an important role in developing students' character, fostering empathy, and creating a more conducive and bullying-free school environment. The consistent implementation of Islamic values can serve as an effective strategy for establishing an Islamic, disciplined, safe, and supportive school culture for all students.